Efficacy of management approaches against cucurbit fruit fly (Bactrocera cucurbitae coquillett) of bitter gourd (Bangladesh Journal of Agricultural Research, 2018)
Field and laboratory studies were carried out to find out the extent of fruit fly infestation at different fruiting stages of bitter gourd as well as to determine the efficacy of some pesticidal and other control approaches applied either separately or in combination. The pesticidal efficacy of three commonly used insecticides such as secufon, malathion, karate and karanja oil as botanicals with the concentrations of 0.25%, 0.50%, 0.75% and 1.00% respectively was determined against the larvae of cucurbit fruit fly, Bactrocera cucurbitae in the laboratory based on mortality at different time intervals. All the pesticides caused maximum mortality at 72 h with 1.00% concentration. The level of fruit fly infestation at different fruiting stages of bitter gourd ranged from 8.91% to 88.19%, 9.24% to 94.89% and 5.01% to 89.27% at early, mid and late fruiting stage, respectively. Soil treatment with furadan @ 10kgha-1 + bagging of fruits showed significantly lowest infestation (9.46%) which was ten times lower than that of untreated control (91.43%). The other control approaches viz., sex pheromone, bait trap with secufon + cucurbit chop, bait trap consisted of secufon + banana chop reduced fruit fly infestation to a significant level. The highest number (83.67) of flies trapped at mid fruiting stage of bitter gourd was recorded in sex pheromone trap while the ratio of male and female flies ranged from 1.13 to 1.24 in the trapped individuals.Bangladesh J. Agril. Res. 42(4): 757-766, December 2017